Pengaruh Keterampilan Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan di PT Sat Nusapersada Tbk - Arlina Zega; Riki Riki (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to determine the effect of work skills and work environment on employee performance at PT. Satnusa Persada Tbk. The type of research used is a quantitative approach with a survey method, namely This research is included as an associative study. Associative research is a study that seeks the relationship or influence of independent variables of skills (X1), work environment (X2), and employee performance (Y) as dependent variables. The population of this study is all employees at PT. Satnusa Persada Tbk. The technique used in this study is purposive sampling. Definition of purposive sampling method "Sampling determination technique with certain considerations, The number of samples in this study is adjusted to the number of statement indicators used in the questionnaire, assuming n x 5 observer variables (indicators) up to n x 10 observed variables (indicators). The number of questions in the research questionnaire is 17 questions; so the minimum number of samples is 5 times the number of questions or 5 x 17 = 85, then the number of samples used is 85 respondents. The results of the study showed the influence of work skills and work environment on employee performance at PT. Satnusa Persada Tbk.. (R Square 424) or 42.4%. From the results of the SPSS Application data processing, it can be concluded that the skill variables (X1), work environment (X2) simultaneously affect the employee performance variable (Y) while 57.6% is influenced by other variables not examined in this study.